Les liens-fnḫ.wy: enquête sur un hapax des Textes des Sarcophages - Séguier, Romain (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
The author revisits the Coffin Texts 1018 in order to explore the word fn ḫ .wy and to determine his meaning. Through the exploration of the context of the spell and the semantics fields surrounding the term, it is possible to partially grasp the writer thought which has leaded to use (or even to create) this hapax. Notions of spatiality and ethnicity, mixed with material realities, storyline and funerary conceptions, feed the deceased’s tribulations on its way to reach Osiris. So, he acquires the protection of fn ḫ .wy -cords, an Aker’s privilege, for accessing his ultimate purpose in the faraway northern celestial land.